Penetrance estimate of LRRK2 p.G2019S Mutation in Individuals of Non-Ashkenazi Jewish Ancestry - Lee, Annie J. (Mov Disord, 2017)
BACKGROUND: Penetrance estimates of the LRRK2 p.G2019S mutation for Parkinson’s disease (PD) vary widely (24%–100%). The p.G2019S penetrance in individuals of Ashkenazi Jewish ancestry has been estimated as 25%, adjusted for multiple covariates. It is unknown whether penetrance varies among different ethnic groups. The objective of this study was to estimate the penetrance of p.G2019S in individuals of non-Ashkenazi Jewish ancestry and compare penetrance between Ashkenazi Jews and non-Ashkenazi Jews to age 80. METHODS: The kin-cohort method was used to estimate penetrance in 474 first-degree relatives of 69 non-Ashkenazi Jewish LRRK2 p.G2019S carrier probands at eight sites from the Michael J. Fox LRRK2 Cohort Consortium. An identical validated family history interview was administered to assess age at onset of PD, current age, or age at death for relatives in different ethnic groups at each site. Neurological examination and LRRK2 genotype of relatives were included, when available. RESULTS: Risk of PD in non-Ashkenazi Jewish relatives who carry a LRRK2 p.G2019S mutation was 42.5% (95% CI: 26.3 – 65.8%) to age 80 which is not significantly higher than the previously estimated 25% (95% CI: 16.7 – 34.2%) in Ashkenazi Jewish carrier relatives. The penetrance of PD to age 80 in LRRK2 p.G2019S mutation carrier relatives was significantly higher than the non-carrier relatives, as seen in Ashkenazi Jewish relatives. CONCLUSIONS: The similar penetrance of LRRK2 p.G2019S estimated in Ashkenazi Jewish carriers and non-Ashkenazi Jewish carriers confirms that p.G2019S penetrance is 25–42.5% at age 80 in all populations analyzed.